The Incidence and Risk Factors for Volar Shear Distal Radius Fractures at a Level 1 Trauma Center - Murgai, Rajan; Martin, Anthony; Minaie, Arya; Ghali, Miriyam; Dodds, Seth D. (Journal of Wrist Surgery, 2025)
The purpose was to determine the incidence of volar shear distal radius fractures at a level 1 trauma center and identify risk factors for this fracture pattern.A retrospective review of all patients who presented to a level 1 trauma center with a distal radius fracture over a 2-year span was performed. Volar shear distal radius fractures can be characterized into two distinct types, partial articular and complete articular. A total of 35 patients with partial articular or complete articular volar shear distal radius fractures were compared with 377 patients who had other types of distal radius fractures. In a second analysis, 17 patients with partial articular volar shear distal radius fractures (AO Type B3) were compared with 395 patients who had other types of distal radius fractures (AO Types A, B1/2, and C). The cohorts were compared for differences in patient demographics and injury mechanism. A multivariate analysis identified significant risk factors for partial articular volar shear distal radius fractures.The incidence of volar shear distal radius fractures was 8.5% (35/412). Patients with volar shear distal radius fractures were younger (40.1 versus 51.5 years, p = 0.003) than patients with other types of distal radius fractures. A high energy mechanism of injury (OR = 5.4, p = 0.0001) and male sex (OR = 3.0, p = 0.003) were significant risk factors for volar shear distal radius fractures. In a subgroup analysis of partial articular volar shear distal radius fractures, younger age, high energy mechanism of injury, and male sex were found to be significant risk factors. In a multivariate analysis, high energy mechanism of injury and younger age remained significant risk factors for partial articular volar shear distal radius fractures.High energy mechanisms of injury and younger age are significant risk factors for volar shear distal radius fractures.Level III, Case Control Study.
Keywords: AO classification; distal radius fracture pattern; risk factor; volar Barton fracture; volar shear distal radius fracture